2021
DOI: 10.1155/2021/2961079
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Glutamylcysteine Alleviates Ischemic Stroke‐Induced Neuronal Apoptosis by Inhibiting ROS‐Mediated Endoplasmic Reticulum Stress

Abstract: Ischemic stroke is a severe and acute neurological disorder with limited therapeutic strategies currently available. Oxidative stress is one of the critical pathological factors in ischemia/reperfusion injury, and high levels of reactive oxygen species (ROS) may drive neuronal apoptosis. Rescuing neurons in the penumbra is a potential way to recover from ischemic stroke. Endogenous levels of the potent ROS quencher glutathione (GSH) decrease significantly after cerebral ischemia. Here, we aimed to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…ER stress, as a protective stress response in eukaryotic cells, can be activated by the imbalanced homeostasis 9 . Once ER stress arises, excessive improperly folded proteins accumulate in the ER lumen 10 . The unfolded protein response (UPR) then occurs, which is sensed and activated by three transmembrane proteins, activating transcription factor 6 (ATF6), inositol requiring enzyme (IRE), and protein kinase RNA (PKR)‐like ER kinase (PERK) 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ER stress, as a protective stress response in eukaryotic cells, can be activated by the imbalanced homeostasis 9 . Once ER stress arises, excessive improperly folded proteins accumulate in the ER lumen 10 . The unfolded protein response (UPR) then occurs, which is sensed and activated by three transmembrane proteins, activating transcription factor 6 (ATF6), inositol requiring enzyme (IRE), and protein kinase RNA (PKR)‐like ER kinase (PERK) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Once ER stress arises, excessive improperly folded proteins accumulate in the ER lumen. 10 The unfolded protein response (UPR) then occurs, which is sensed and activated by three transmembrane proteins, activating transcription factor 6 (ATF6), inositol requiring enzyme (IRE), and protein kinase RNA (PKR)-like ER kinase (PERK). 11 URP plays a crucial role in the restoration of ER homeostasis.…”
mentioning
confidence: 99%
“…A previous study has revealed that the promotion of ERS via knockdown Hes1 induced vast neuronal apoptosis in a mouse model with middle cerebral artery occlusion (MCAO) [ 25 ]. In addition, Li et al reported that the inhibition of ERS signal pathway by γ -glutamylcysteine attenuated neuronal apoptosis in the ischemic brain of mice [ 28 ]. The aforementioned results support the idea that ERS may be a potential target in IS injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, consuming pre-formed glutathione is an inefficient way to raise cellular levels of glutathione since published clinical studies demonstrate that it may take weeks or months to impact cellular levels when elevated levels are most needed acutely. [31][32][33][34][35][36][37][38][39][40][41][42][43] concept should be considered and tested using this approach in conjunction with measuring blood biomarkers that reflect individual and pathway proteins that correspond to inflammation and oxidative stress.…”
Section: American Journal Of Biopharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%